Sistem Pemantauan Energi Penggunaan Listrik Pada Bangunan Pintar Dengan Sistem Iot (Internet Of Things) - Rahman, M. Fadhilur; Ilyas, Tufanul; Armando, Romie (LPPM STIKOM Tunas Bangsa, 2024)
This research aims to develop an energy monitoring system for electricity usage in smart buildings using the Internet of Things (IoT). Smart buildings represent a concept where information and communication technologies are utilized to manage energy resources, including electricity consumption efficiently. This system indirectly assists humans by ensuring precise and controlled monitoring. The methodology in this research involves the development of an integrated sensor system connected to IoT devices to monitor electricity consumption in real time. These sensors will be strategically placed at key points within the building, such as the main electrical panels and critical electronic devices, to measure and transmit energy consumption data to the IoT platform.